How do we design an Habitat? Influence and implications of urban design in territorial, social, economic and environmental sustainability - Lopes, S. S.; Borges, J.C.; Fernandes del Pino, R.; Marat-Mendes, T. (Cidades, Comunidades e Territórios, 2023)
This thematic dossier of the journal CIDADES, Comunidades e Territórios proposes a space for reflection and discussion, national or international, of housing and habitat, focusing particularly on the “influence and implications of urban design in territorial, social, economic and environmental sustainability”, a mighty long subtitle that aims to express the complex and multifold aspects that need to be contemplated when approaching the habitat notion.